IMPLEMENTASI INOVASI PELAYANAN PALEM MERAH DALAM MENINGKATKAN PELAYANAN PUBLIK DI KELURAHAN CIKIWUL - Mita Widyastuti; Rani Intan; Alifa Dhiya Rahadi; Muhammad Agus Setiawan (Jurnal Ekonomi dan Bisnis, 2025)
The Palem Merah service innovation was developed to expand access to population administration for residents of Cikiwul who are unable to visit the office during regular working hours. The issues underlying this program include limited daytime service hours, irregular queues, and difficulties faced by residents in completing administrative requirements that must be processed in person. This study aims to describe the mechanism of the Pelayanan Malam Sabtu Meriah, explain its impact on service speed and data accuracy, and outline the operational challenges encountered by administrative officers. The study employs a qualitative method with data collected through in-depth interviews and literature review. The findings show that Palem Merah shortens document processing time, improves the accuracy of population data, and provides convenience for vulnerable groups through a door-to-door service. The success of the program is influenced by the readiness of the officers, technological support, and a well-coordinated service schedule. The program remains sustainable because officers perceive the evening duties as part of their public service responsibilities.